Improving Fraction Learning Using Course Review Horay and Puzzle Media: Meningkatkan Pembelajaran Pecahan Menggunakan Ulasan Kursus Horay dan Media Puzzle - Rada Umar; Zulqoidi R Habibie; Sundahry (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mathematics education is vital for developing students' critical and analytical thinking skills. Specific Background: However, traditional lecture-based instruction and lack of engaging media have resulted in low participation and poor learning outcomes, especially in topics like fractions. Knowledge Gap: Prior studies have evaluated the Course Review Horay model and concrete media separately, but few have investigated their integrated use in elementary settings. Aims: This study aimed to improve the learning process and outcomes of fourth-grade students on fractions through the integration of the Course Review Horay model with fraction puzzle media. Results: Conducted as a Classroom Action Research in two cycles with 16 students, the intervention led to a significant increase in active participation (from 12.5% to 62.5% categorized as “Very Good”) and mastery learning (from 60% to 81.25%), supported by a statistically significant t-test result (p = 0.032 < 0.05). Novelty: The combination of a collaborative, gamified model with tactile media offers a novel and engaging method for teaching abstract concepts. Implications: This integrated approach supports 21st-century learning goals and is a practical strategy for enhancing both engagement and achievement in primary mathematics education.Highlight : Model Course Review Horay's fraction puzzle helps increase student engagement and learning outcomes. Student engagement in the “Very Good” category rose from 0% to 62.5%. The average student score increased from 70.94 to 75.63 with a completion rate of 81.25%. Keywords : Student Engagement, Learning Outcomes, Mathematics Education, Course Review Horay Model, Fraction Puzzle Media